Reaching subculture markets: The cryptic marketing approach. Issue 2 (17th February 2021) - Choong, Kelly; Drennan, Judy; Weeks, Clinton S.; Weber, Ian
ABSTRACT: The growing importance of subcultures in society has changed the way organisations communicate with consumers. Differences in values and norms suggest brands must strategically communicate with these audiences to engage and build trust. However, if the targeted subculture market is stigmatised, the risk of alienating other sections of society is a serious concern for marketers. This paper, therefore, conceptually examines how marketers can reach subculture markets without the risk of estranging the wider market. In particular, it considers this issue through the lens of cryptic marketing, which has the capacity to simultaneously overcome loss of brand trust and attract the attention of a target audience.